An experimental investigation on the evaporation characteristics of lubricating oil film in different grooves. (January 2020) - Qian, Yejian; Hu, Qiancheng; Li, Zhaoyuan; Meng, Shun; Zhu, Kongjin; Cheng, Xiaozhang; Tao, Changfa
Abstract: The pre-ignition of lubricating oil is the main cause of super knock in gasoline direct injection (GDI) engine. This paper investigates the effect of thermal radiation, cylinder material and film thickness on evaporation characteristics of lubricating oil film using a radiation device under the condition of open space. The experimental results show that the mass loss rate of lubricating oil film is proportional to the film thickness. The thermal conductivity of the material which coated with lubricating oil film has a significant influence on the evaporation characteristics of oil film. There are three obvious stages in the mass change curve of lubricating oil film and a formula is developed to estimate the mass loss rate of the lubricating oil film during the second stage.